Application of the Learning Cycle Model with Video Media in Improving the Quality of Learning IPS For Students - Nurlaini Nurlaini (Eduvest - Journal of Universal Studies, 2021)
Improving the quality of social studies learning consists of improving teacher skills, student activities, and learning outcomes. Data on student learning outcomes showed as many as 21 students (70%) of the 30 students did not complete the KKM (64). This happens because the teacher has not been optimal in using learning models and media, causing student activity and learning outcomes to be low. Therefore, it is necessary to improve the quality of social studies learning through the application of the Learning Cycle model with video media. The purpose of this study was to improve the quality of social studies learning through the Learning Cycle model with video media for fifth grade students at SDN 32 Sungai Jaring. This study used classroom action research which was carried out in three cycles, each cycle consisting of one meeting with four stages, namely planning, implementation, observation, and reflection. The results of the reflection as planning for the next cycle. The subjects of this study were teachers and 30 fifth grade students at SDN 32 Sungai Jaring. Data collection techniques using test and non-test techniques were analyzed with descriptive and qualitative descriptive statistical techniques. The results showed that the teacher's skills in the first cycle obtained good criteria, the second cycle obtained very good requirements, and the third cycle obtained very good requirements. Student activities in cycle I got good criteria, cycle II got good criteria, and cycle III got very good criteria. Student learning outcomes in cycle I obtained sufficient criteria, cycle II obtained good criteria, and cycle III obtained excellent criteria. The conclusion of this research is the Learning Cycle model with video media can improve the quality of social studies learning for class V SDN 32 Sungai Jaring.